2017
DOI: 10.1016/j.healthplace.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of spatially-derived access-to-care characteristics in melanoma prevention and control in Los Angeles county

Abstract: Among 10,068 incident cases of invasive melanoma, we examined the effects of patient characteristics and access-to-care on the risk of advanced melanoma. Access-to-care was defined in terms of census tract-level sociodemographics, health insurance, cost of dermatological services and appointment wait-times, clinic density and travel distance. Public health insurance and education level were the strongest predictors of advanced melanomas but were modified by race/ethnicity and poverty: Hispanic whites and high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Areas with a higher density of dermatologists are correlated with the earlier diagnosis of melanoma [ 128 , 129 , 130 ]. One spatial analysis study found that a low density of clinics corresponded to a 30% increase in the risk for thick lesions [ 128 ].…”
Section: Socioeconomic Risk Factors For Melanoma Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Areas with a higher density of dermatologists are correlated with the earlier diagnosis of melanoma [ 128 , 129 , 130 ]. One spatial analysis study found that a low density of clinics corresponded to a 30% increase in the risk for thick lesions [ 128 ].…”
Section: Socioeconomic Risk Factors For Melanoma Developmentmentioning
confidence: 99%
“…Areas with a higher density of dermatologists are correlated with the earlier diagnosis of melanoma [ 128 , 129 , 130 ]. One spatial analysis study found that a low density of clinics corresponded to a 30% increase in the risk for thick lesions [ 128 ]. The distance to dermatologist clinics increased the risk of thick tumors for White Hispanic individuals and poorer communities, which highlights the issue of a lack of accessibility to treatment due to racial and socioeconomic disparities [ 128 ].…”
Section: Socioeconomic Risk Factors For Melanoma Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…area-based measures of poverty, education, racial/ethnic composition and acculturation) (McKernan et al, 2015), potential access (i.e. health insurance coverage, wait time and affordability of services) and spatial access (travel distance and neighborhood-level density of physicians) (Escobedo et al, 2017). In China, the real condition is more complex.…”
Section: Introductionmentioning
confidence: 99%